A study of interface adhesion between polyamide 6 (PA6) and nitrile rubber (NBR)1. (21st March 2014) - Wang, Yuan; Ghita, Oana; Kavanagh, Dave; Chandler, Duncan; Abel, Marie‐Laure; Rossi, Antonella; Watts, John F.
<x xml:space="preserve">Abstract</x> The mechanism of interface bonding of a selected nitrile rubber compound vulcanized on polyamide 6 was studied using transmission electron microscopy. The two types of interfaces identified were formed through mechanical clamping and enhanced by hydrogen bonding between polyamide 6 and silane coupling agent in nitrile rubber compound. Copyright © 2014 John Wiley & Sons, Ltd.